Photoshop CS5 down and dirty tricks - Barker, Corey (Kelbytraining.com : Peachpit Press, 2010)
"This course is a collection of some of the coolest Photoshop effects being used today in movies, TV, magazines, and the web. Exploring everything from light and brush effects to full image composites and 3D effects. While along the way utilizing some of the coolest new features in Photoshop CS5. This is the course that will motivate and inspire you to push Photoshop to its limits"--Resource description page.